2014
DOI: 10.1074/jbc.m114.608562
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Anchor at an Invariant Hormone-Receptor Interface

Abstract: Background: Invariant insulin residue Phe B24 (a site of diabetes-associated mutation) contacts the insulin receptor. Results: Hormonal function requires hydrophobicity rather than aromaticity at this site. Conclusion: The B24 side chain provides a nonpolar anchor at the receptor interface. Significance: Nonstandard aliphatic modification of residue B24 may enhance therapeutic properties of insulin analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 86 publications
0
23
0
Order By: Relevance
“…These are: initial detachment (opening) of the B-chain C-terminal (BC-CT) of insulin from its hydrophobic (helical) core to expose key binding residues (see Fig 1 A and 1 B ), followed by a rotation and re-modeling of the αCT portion of IR upon the surface of the β-sheet of the L1 domain of IR, and lastly docking of the insulin B-chain α-helix in a parallel orientation to the αCT segment, creating strong hydrophobic interactions in between. Extensive mutagenesis and structural studies of insulin substantiate the critical role of the BC-CT, and in particular the residues F24–Y26, in binding to IR [ 17 , 18 , 21 25 ]. Furthermore, the first crystal structure of the insulin–IR complex has revealed the extent of the structural changes and the importance of the BC-CT residues of insulin, especially F24-Y26, as well as the crucial role of H710 and F714 of the αCT segment [ 14 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are: initial detachment (opening) of the B-chain C-terminal (BC-CT) of insulin from its hydrophobic (helical) core to expose key binding residues (see Fig 1 A and 1 B ), followed by a rotation and re-modeling of the αCT portion of IR upon the surface of the β-sheet of the L1 domain of IR, and lastly docking of the insulin B-chain α-helix in a parallel orientation to the αCT segment, creating strong hydrophobic interactions in between. Extensive mutagenesis and structural studies of insulin substantiate the critical role of the BC-CT, and in particular the residues F24–Y26, in binding to IR [ 17 , 18 , 21 25 ]. Furthermore, the first crystal structure of the insulin–IR complex has revealed the extent of the structural changes and the importance of the BC-CT residues of insulin, especially F24-Y26, as well as the crucial role of H710 and F714 of the αCT segment [ 14 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, all the previous experimental and computational studies on insulin focused on the structural changes that occur in the BC-CT during activation and on mutations in the critical residues, F24 (all the residues mentioned without extra labelling belong to chain B. The A chain residues are denoted by a subscript A) and Y26 [ 15 , 17 19 , 21 25 , 27 , 28 ]. Two key questions regarding the activation of insulin remain unanswered: the frequency of the BC-CT opening, which is necessary for insulin to bind to the IR, and the mechanism that triggers this opening.…”
Section: Introductionmentioning
confidence: 99%
“…In both mutant insulin Los Angeles and Chicago, aromatic amino residue phenylalanine substituted by non-aromatic serine and leucine respectively leads to changes in binding interaction with IR. The charged or polar side chains reduce the hormone binding (Pandyarajan et al, 2014) and in insulin Los Angeles, the number of polar side chains are increased and this may reduce the binding affinity towards IR.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rapid rise in the number of diabetic people, there is great deal of interest in the development of insulin analogues with enhanced activity and affinity, which can be used for therapeutic purposes. Extensive mutagenesis and structural studies revealed the significant role of the BC-CT—and in particular the triplet of the B-chain aromatic residues F24 B , F25 B and Y26 B —in the activation process of insulin and the binding interface [16] , [22] , [23] , [24] , [25] , [26] , [29] , [30] , [31] , [46] , [47] , [48] , [49] . The F24 B residue has been shown to act as a hinge as the BC-CT opens during the activation of insulin (BC-CT opening) [23] , [25] , [26] , [30] , [46] , while the Y26 B residue has been shown to be a critical residue for the activation of insulin [26] , [30] , [31] , [47] , [48] , [49] .…”
Section: Introductionmentioning
confidence: 99%
“…Although a significant number of experimental studies focus on insulin and its complex structure with the IR [16] , [17] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [31] , [32] , [33] , [46] , [47] , [48] , [49] , [50] , as well as on mutations on the critical residues of insulin for predicting potential therapeutic candidates [23] , [25] , [26] , [27] , [31] , [46] , [47] , [48] , [49] , there are still a lot of key features that cannot be solved or are hard to explain using only experimental approaches. There have been relatively few computational studies investigating the conformational changes and dynamics of insulin [25] , [30] , [31] , [51] , [52] , and even less focusing on insulin mutations [25] , [31] , [53] , [54] .…”
Section: Introductionmentioning
confidence: 99%